DIVERSITY OF FISH TYPES IN CIRAHAB SOURCE WATER AND WATER QUALITY FOR FISH ECOSYSTEMS IN CIRAHAB, CURUGGOONG VILLAGE PADARINCANG DISTRICT, SERANG-BANTEN - Hermawan, Hermawan (Transpublika Publisher, 2024)
The research was conducted at water sources in Cirahab, Curuggoong village, Padarincang District, Serang-Banten Regency, research was conducted in January 2024, this research was conducted to determine the diversity of fish in the water source water ecosystem in Cirahab. The results obtained in the research There are 11 types of fish obtained during the research, including tilapia, goldfish, wader, betook, eel, nilem, chana, tawes, sili-sili, kampala (paitan) and catfish. The fish that dominate the waters of Cirahab are the wader fish which are often found there. Fishing is found in 3 places, namely places number 1, 2 and number 3. The category obtained in the fish diversity index is the